Chinese herbal medicine for threatened miscarriage: An updated systematic review and meta-analysis - Xie, Hongliang; Zhang, Aolin; Mou, Xuan; He, Tao; Li, Junwei; Wang, Chi Chiu; Fan, Xiaohui; Li, Lu (Frontiers in Pharmacology, 2023)
Objective To conduct an updated systematic review and meta-analysis on the efficacy and safety of Chinese herbal medicine (CHM) for threatened miscarriage. Data Sources Electronic databases were searched from inception to June 30, 2022. Study Eligibility Criteria Only randomized controlled trials (RCTs) that assessed the efficacy and safety of CHM or combined CHM and Western medicine (CHM-WM) and compared with other treatments for threatened miscarriage were included for analysis. Methods Three review authors independently evaluated included studies, assessed the risk of bias and extracted data for meta-analysis, sensitivity analysis (β-hCG level) and subgroup analysis (TCM syndrome severity, β-hCG level). The risk ratio and 95% confidence interval were calculated by RevMan. Certainty of the evidence was assessed according to GRADE. Results Overall, 57 RCTs involving 5881 patients met the inclusion criteria. Compared with WM alone, CHM alone showed significant higher incidence of continuation of pregnancy after 28 gestational weeks (Risk Ratio (RR) 1.11; 95% CI 1.02 to 1.21; n=1; moderate quality of evidence), continuation of pregnancy after treatment (RR 1.30; 95% CI 1.21 to 1.38; n=10; moderate quality of evidence), higher β-hCG level (Standardized Mean Difference (SMD) 6.88; 95% CI 1.74 to 12.03; n=4) and lower Traditional Chinese medicine (TCM) syndrome severity (SMD -2.94; 95% CI -4.27 to -1.61; n=2). Compared with WM alone, combined CHM-WM showed significant higher incidence of continuation of pregnancy after 28 gestational weeks (RR 1.21; 95% CI 1.16 to 1.27; n=15; moderate quality of evidence), continuation of pregnancy after treatment (RR 1.19; 95% CI 1.16 to 1.23; n=41; moderate quality of evidence), higher β-hCG level (SMD 2.27; 95% CI 1.72 to 2.83; n=37) and lower TCM syndrome severity (SMD -1.74; 95% CI -2.21 to -1.27; n=15). No significant differences in reducing the adverse maternal outcomes and neonatal death were found in combined CHM-WM compared with WM alone (RR 0.97; 95% CI 0.62 to 1.52; n=8; RR 0.39; 95% CI 0.12 to 1.21; n=2). Conclusion Current evidence supported CHM could be a potential treatment for threatened miscarriage. However, results should be interpreted with caution considering the low to moderate quality of the available evidence.